An Information System Design Development “OKE ANIMAL” for Animal Clinic DISNAKKAN Kabupaten Ciamis Using The Prototype Method - Silvia, Ayu; Safitri, Sisilia Thya (LPPM Institut Teknologi Telkom Purwokerto, 2023)
This study presents a comprehensive investigation into the development and evaluation of an information system designed to streamline administrative record-keeping within the veterinary clinic of DISNAKKAN Ciamis. The observation phase, involving in-depth discussions with veterinary clinic staff, underscored the imperative need for an information system to enhance the management of patient data, medical records, and cirobis records. Significantly, this system is custom-tailored to accommodate the unique background of veterinary clinic officers, ensuring user-friendliness and swift adoption. The literature study buttressed the case for digital record-keeping, offering a compelling argument for minimizing data discrepancies through digital database recording. The prototype method was employed to guide the development process, commencing with extensive communication and quick planning. UML diagrams provided a roadmap for system functionality. The resulting prototype system, featuring login mechanisms, data entry forms, and data display components, was designed to elevate administrative efficiency. The deployment of the system and its usability assessment using the SUS method shed light on the user experience. This research marks a significant stride in enhancing administrative record management at the veterinary clinic of DISNAKKAN Ciamis, improved data management and record-keeping, while setting a valuable precedent for future system development in similar contexts.